2006
DOI: 10.1103/physrevlett.97.123003
|View full text |Cite|
|
Sign up to set email alerts
|

High Harmonic Generation and Molecular Orbital Tomography in Multielectron Systems: Beyond the Single Active Electron Approximation

Abstract: Access and use of this website and the material on it are subject to the Terms and Conditions set forth at High harmonic generation and molecular orbital tomography in multielectron systems: beyond the single active electron approximation Patchkovskii, Serguei; Zhao, Zengxiu; Brabec, Thomas; Villeneuve, D. NRC Publications Record / Notice d'Archives des publications de CNRC:http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=12328441&lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(63 citation statements)
references
References 18 publications
1
62
0
Order By: Relevance
“…This error is also observed in the previous works especially for the σ orbital. Besides the limited spectrum range, the imaging errors may also result from several other reasons, such as the discrete sampling in the frequency domain with the interval of 2ω L , and the SFA and singleactive-electron approximation used in the theoretical model [7][8][9][10]12]. In the MOT process, when the Stark phase is approximately subtracted by using the analytical expression derived in [18], the main structure of the target orbital is also successfully reproduced in both the length and velocity forms.…”
Section: Tomographic Reconstructionmentioning
confidence: 95%
See 1 more Smart Citation
“…This error is also observed in the previous works especially for the σ orbital. Besides the limited spectrum range, the imaging errors may also result from several other reasons, such as the discrete sampling in the frequency domain with the interval of 2ω L , and the SFA and singleactive-electron approximation used in the theoretical model [7][8][9][10]12]. In the MOT process, when the Stark phase is approximately subtracted by using the analytical expression derived in [18], the main structure of the target orbital is also successfully reproduced in both the length and velocity forms.…”
Section: Tomographic Reconstructionmentioning
confidence: 95%
“…By applying this method to a series of aligned molecules, they accomplished a tomographic reconstruction of the highest occupied molecular orbital (HOMO) of N 2 . Since then, the MOT has attracted a great deal of attention for its great significance in uncovering the basic properties of molecules and chemical reactions [7][8][9][10][11][12][13]. In most of the works, the target molecular orbitals are symmetric with either gerade or ungerade symmetry, while the MOT of nonsymmetric orbitals is more difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Different channels of ionization can thus be expected to play role, as well as the electron-electron correlations [147,148].…”
Section: High Harmonic Generation: Multielectron Effectsmentioning
confidence: 99%
“…Works on the role of electron exchange and spin statistics of electrons in the molecule [147,148] showed that molecular orbital tomography, first described in [92], reconstructs the Dyson orbital of the molecule together with the effects of the electron correlations, imaging signatures of lower orbital as well as HOMO. Dyson orbital is an overlap between the wave function of the ground…”
Section: High Harmonic Generation: Multielectron Effectsmentioning
confidence: 99%
“…There has been a focus on diatomic molecules because of their relative simplicity and the ability to align them relative to the laser polarization [7]. For the case of single-photon ionization, or recombination leading to harmonic emission, it was shown that the measurements reflect the Dyson orbital associated with the ionization [8]. In the case of tunnel ionization of groundstate diatomic molecules, while there is no direct formalism that relates the angle-resolved ionization yields to the molecular orbital structure, the ionization yield as a function of the angle between the laser polarization vector and the molecular axis has been shown to reflect the shape of the orbital from which an electron was removed, i.e., the hole left following ionization [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%